2003
DOI: 10.1081/ada-120020514
|View full text |Cite
|
Sign up to set email alerts
|

Mediators Of Effectiveness In Dual-focus Self-help Groups

Abstract: Although research on the effectiveness of 12-step group participation has been increasing, there has been little examination of the processes by which such participation leads to positive outcomes. Two kinds of factors have been proposed as mediating between 12-step group affiliation and outcomes for members, common process factors that have been identified in a range of behavioral treatments and factors that are relatively unique to the 12-step model. The study tested the hypotheses that two common process fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 75 publications
1
48
0
Order By: Relevance
“…This results in decreased referral rates by mental health professionals of patients with addictions to these programs (Magura et al, 2003). This misunderstanding exists within a broader historical mutual suspicion between many members of Twelve Step programs and health professionals, although this divide has narrowed (BenAri, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…This results in decreased referral rates by mental health professionals of patients with addictions to these programs (Magura et al, 2003). This misunderstanding exists within a broader historical mutual suspicion between many members of Twelve Step programs and health professionals, although this divide has narrowed (BenAri, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Polcin and Zemore (2004) and Zemore and Kaskutas (2004) studied ambulatory patients who were predominantly drawn from AA meetings by applying a multidimensional measurement of religiousness/spirituality, and they found that those AA members who had longer periods of sobriety reported a greater level of spirituality at the time of evaluation. Magura et al (2003) reported that responses on a 12-item Spirituality Well-Being scale were not associated with increased abstinence, but were associated with health-promoting behaviors such as btaking care of yourselfQ and bgetting enough sleep.Q Some studies on ambulatory patients on recovery, however, did not show a relationship between spiritual orientation and decreased use of drugs. Christo and Franey (1995) evaluated a sample of patients attending Narcotics Anonymous in London and found, on a 6-month follow-up, no relationship between scores on a spiritual belief questionnaire and abstinence.…”
Section: Introductionmentioning
confidence: 98%
“…Taking into account the relationship between DTR involvement and health maintenance behavior, internal locus of control, sociability, installation of hope, and spirituality all mediated the relationship. These findings are not surprising given that internal locus of control increases individuals' self-efficacy for recovery and sociability facilitates the formation of meaningful relationships and mutual aid in the recovery process (Magura et al, 2003).…”
Section: Processmentioning
confidence: 90%
“…In their investigation of the DTR groups, Magura et al (2003) found that the degree of involvement in DTR groups and their sponsoring organization (frequency of attendance, sharing at meetings, chairing meetings, speaking with other group members about issues) was significantly positively associated with drug and alcohol abstinence and associated health maintenance behaviors (medication adherence, keeping doctor's appointments, self-care). Furthermore, higher internal locus of control and degree of participant sociability mediated the relationship between DTR involvement and abstinence.…”
Section: Processmentioning
confidence: 97%